Unappreciated duty : the forgotten contribution of New Zealand’s Defence Stores Department in mobilising the New Zealand Expeditionary Force in 1914 : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in History at Massey University, Manawatu, New Zealand - McKie, Robert (Massey University, 2022)
Historians have generally focused on the period leading up to New Zealand’s entry into the First World War by examining New Zealand’s military’s command, organisational, and training structures. For example, the evolution of New Zealand’s military in the wake of the South Africa war and the contribution of imperial officers in shaping and welding it into a well-trained and equipped force is well recorded. However, the contribution and impact of New Zealand’s military logistic services have remained unexplored and under-researched. This thesis utilises a wide range of primary and secondary sources to examine the Defence Stores Department and its essential role in providing material and maintenance support to New Zealand’s military forces from the 1860s to the mobilisation of 1914. In examining the evolution of the Defence Stores Department, it is shown that this department's long experience in the management and maintenance of military materiel had positive outcomes for New Zealand's military forces, including the mobilisation of the New Zealand Expeditionary Force and ongoing support to New Zealand’s war effort during World War One.
Copyright holders of copyrighted images may request their removal via the Copyright Take Down Request link below.
Keywords: 430320 New Zealand history